Case Report of Radial Nerve Palsy Patients Treated with Additional Jungsongouhyul Pharmacopuncture - Eun-Hee Choi; Hea-Sun Chun; Hye-Seon Ryu; Ju-Hee Lee; Dong-Seon Yang; Seok Hong (Korean Pharmacopuncture Institute, 2011)
Objectives: This study was to investigate the clinical effect of additional Jungsongouhyul Pharmacopuncture on radial nerve palsy patients. Methods & Results: The patients were hospitalized or outpatients in Department of traditional korean medical hospital, Dongshin University from 28th, Oct. 2009 to 25th, Aug, 2010. All patients were treated by additional Jungsongouhyul Pharmacopuncture. To evaluate the wrist drop and numbness of fingers, coding result, Verbal numerical scale (VNS) were used. As the result, symptoms are improved remarkably according to improvement of coding result, VNS score. Conclusions: Patients were treated during 3.5 weeks in average. All cases were excellent results by additional Jungsongouhyul Pharmacopuncture. But further studies are required to investigate exact effects.